DIVERSIFIKASI KEFIR BERBASIS KEDELAI DENGAN VARIASI KONSENTRASI SUSU SKIM DAN INOKULUM - Tina Nurkhoeriyati; Dionisius Yusuf; Ihsan Iswaldi; Abdi Christia; Vania Gisella (Jurnal Teknologi dan Industri Pangan, 2017)
Physicochemical and sensory characteristics of commercial kefir were evaluated to be used as the benchmark for the development of soybean-based kefir with various concentrations of skim milk and inoculum. The commercial kefir has alcohol content and titratable acidity values in accordance with the Codex standards. A Quantitative Descriptive Analysis (QDA) was carried out to obtain the description of kefir as the reference for the development of soybean-based kefir. Sensory evaluation of soybean-based kefir samples with various concentrations of skim milk and inoculum was conducted by trained panelists. Based on sensory evaluation, the soybean-based kefir with similar sensory characteristics to the commercial kefir was that made by adding 10% of skim milk and 10% kefir grains of 3, 4 and 5% (w/w). Soybean-based kefir with 10% (w/w) skim milk and 3% (w/w) kefir grains was chosen for analysis of its physicochemical characteristics. Despite having sensory characteristics similiar to commercial kefir, this soy-based kefir possesses different physicochemical properties from that of commercial one. Neverthe-less, the physico-chemical characteristics of selected kefir-based soybean met the Codex standards. The content of protein, fat, alcohol, dry matter and viscosity of the selected soy-based kefir were: 3.79±0.10% wb, 0.00±0.00% wb, 0.93±0.00%wb, 57.26 mg/kg, 8.43±0.38% wb, and 37.95±0.05 cP, respectively.